2003
DOI: 10.1245/aso.2003.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency Tissue Ablation: Effect of Hepatic Blood Flow Occlusion on Thermal Injuries Produced in Cirrhotic Livers

Abstract: Ablation area is increased significantly with hepatic blood flow occlusion in the human cirrhotic liver. This result may have application in the treatment of larger (>3 cm) hepatic malignancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…Similar increases ranging from two‐ to six‐fold have been demonstrated with various other techniques of thermal ablation, namely radiofrequency ablation and microwave coagulation 3,7–9 . A number of clinical studies report increased ablation volumes with hepatic blood flow occlusion at open or laparoscopic surgery 6,19,25–28 . These studies generally describe imaging results without providing direct histological evidence of significant increases in the volume of necrosis with blood flow occlusion.…”
Section: Discussionmentioning
confidence: 61%
“…Similar increases ranging from two‐ to six‐fold have been demonstrated with various other techniques of thermal ablation, namely radiofrequency ablation and microwave coagulation 3,7–9 . A number of clinical studies report increased ablation volumes with hepatic blood flow occlusion at open or laparoscopic surgery 6,19,25–28 . These studies generally describe imaging results without providing direct histological evidence of significant increases in the volume of necrosis with blood flow occlusion.…”
Section: Discussionmentioning
confidence: 61%
“…The consensus from those experiments is that blood vessels larger than 3-4 mm adjacent to or embedded within ablation zones cause substantial local "heat sink effect" on radiofrequency ablation zones but little to no effect on microwave ablation zones created by using either 915-MHz or 2.45-GHz devices (14)(15)(16)(17)(18)(19)(20)(21). Also, temporary occlusion of regional or global hepatic blood flow causes an increase in the overall size of ablation zones created by radiofrequency and microwave ablation devices (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)13,17,22,23). The studies of the change in hepatic blood flow within the normal physiological range have demonstrated as much as a threefold decrease in radiofrequency ablation zone volume as hepatic blood flow reaches upper physiological rates (11,25) but little to no effect of physiological fluctuations in hepatic blood flow on ablation zone volume created by 915-MHz microwave ablation devices (25).…”
Section: Implication For Patient Carementioning
confidence: 99%
“…Facilitating hepatic resection by blood flow interruption becomes of significance in facilitating minimally invasive or robotic techniques. However, blood flow interruption in the liver may have wider implications in the fields of ablative therapies for liver masses and for chemotherapy and gene therapy 12,13 . Blood flow interruption to enhance ablative therapies for liver tumours has been advocated but hindered by the absence of a safe and simple means of providing it 14 .…”
Section: Discussionmentioning
confidence: 99%